Tinjauan Putusan Pengadilan terhadap Tindak Pidana Orang Tua Penganiaya Anak Tiri hingga Tewas (Studi Kasus di Medan) - Saribu, Marcella Camelia Putri Dolok; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A case of abuse that resulted in the death of a stepchild in Medan involved stepparents who were sentenced to various punishments. This tragic incident occurred when the stepchild became a victim of physical violence by her stepmother and biological father. As a result of the ongoing abuse, the child suffered severe injuries that led to her death. During the trial, the court decided on varying sentences for both perpetrators, with the stepmother receiving a heavier sentence due to her dominant role in the violence, while the biological father was sentenced to a lighter sentence. This case raises the issue of domestic violence, especially against children, and the importance of protecting children from domestic violence. This legal decision is expected to provide a deterrent effect and increase public awareness of the importance of supervision and protection of children.